Ekstraksi Glukomanan dari Umbi Gembili (Dioscorea esculenta L.): Extraction of Glucomannan from Gembili Bulbs (Dioscorea esculenta L.) - Pratiwi Listyana Sareu; Nurhaeni; Ahmad Ridhay; Moh. Mirzan; Syamsuddin (KOVALEN: Jurnal Riset Kimia, 2021)
Gembili bulbs (Dioscorea esculenta L.) have a fairly high carbohydrate content, so they can potentially be a new source of glucomannan compounds. This study aims to determine the yield and glucomannan characteristics of Gembili bulbs at different extraction times and temperatures. Glucomannan was obtained by extraction with water at temperatures of 45, 60, 75, 90, and 105oC for 45, 60, 75, 90, and 105 minutes, and precipitated with isopropyl alcohol. The results showed that the highest yield was obtained at the extraction time of 90 minutes and a temperature of 105oC of 53.09%. The glucomannan of Gembili bulb has a molecular weight of 1,865 x 104 g/mol with ash and water content values of 0.866% and 10.45%, respectively. The results of identification of functional groups with an FTIR spectrophotometer showed that there was a functional group stretching vibration of glucomannan compounds, including the –OH group at a wavenumber of 3431 cm-1 and -C-O-C (glycosidic bond) at a wavenumber of 1020.34 cm-1 and bending vibration of -CH functional groups on wavenumber of 850.61 cm-1.